PENGARUH ASIMETRI INFORMASI, LEVERAGE, DAN KEPEMILIKAN MANAJERIAL PADA MANAJEMEN LABA - Pramesti, Ida Ayu Jayatri; Budiasih, I Gst. Ayu Nyoman (E-Jurnal Akuntansi; Vol 21 No 1 (2017), 2017)
Changes of information on the net profit of a company through various means will provide sufficient impact effect on the follow-up information users of such earnings, one way to perform earnings management (earnings mangement). The purpose of this study was to determine the effect of several variables expected to affect earnings management, including the asymmetry of information, leverage, and managerial ownership. This research was conducted at all manufacturing companies in Indonesia Stock Exchange 2011-2015 period. The samples used as many as 33 companies from the population of 123 companies, through a purposive sampling method. The data collection is done by using the method of observation nonparticipant. The analysis technique used is the technique of multiple linear regression analysis with IBM SPSS 19. The results showed that the asymmetry of information and leverage positive effect on earnings management, while managerial ownership negative effect on earnings management.
Keywords: information asymmetry; leverage; managerial ownership; earnings management